IL1 Pathway in HPV-Negative HNSCC Cells Is an Indicator of Radioresistance After Photon and Carbon Ion Irradiation Without Functional Involvement - Tiwari, Dinesh Kumar; Hannen, Ricarda; Unger, Kristian; Kohl, Sibylla; Heß, Julia; Lauber, Kirsten; Subtil, Florentine S. B.; Dikomey, Ekkehard; Engenhart-Cabillic, Rita; Schötz, Ulrike (Frontiers in Oncology, 2022)
Background: Treatment of locally advanced HPV-negative head and neck squamous cell carcinoma (HNSCC) with photon radiation is standard of care but shows only moderate success. Alterations in response towards DNA DSB repair, apoptosis and senescence are underlying determinants of radioresistance in the tumor cells. Recently, senescence and the associated secretory phenotype (SASP) came into the focus of research and raised the need to identify the tumor-promoting molecular mechanisms of the SASP. The aim of this project was to unravel more of this process and to understand the impact of the IL1 pathway, which plays a major role in SASP. The studies were performed for photon and 12C-ion irradiation, which strongly vary in their effect on radioresistance. Materials and Methods: A panel of five HPV-negative HNSCC cell lines was treated with photon and 12C-ion irradiation and examined for clonogenic survival, DNA DSB repair and senescence. SASP and IL1 gene expression were determined by RNA sequencing and activation of the IL1 pathway by ELISA. A functional impact of IL1A and IL1B was examined by specific siRNA knockdown. Results: Cell killing and residual DSBs were higher after 12C-ion than after photon irradiation. 12C-ion induced more senescence with a significant correlation with cell survival. The impact on radioresistance appears to be less than after photon irradiation. Expression of SASP-related genes and the IL1 pathway are strongly induced by both types of irradiation and correlate with radioresistance and senescence, especially IL1A and IL1B exhibit excellent associations. Surprisingly, knockdown of IL1A and IL1B revealed that the IL1 pathway is functionally not involved in radioresistance, DSB repair or induction of senescence. Conclusions: IL1A and IL1B are excellent indicators of cellular radioresistance and senescence in HNSCC cells without functional involvement in these processes. Clearly more research is needed to understand the molecular mechanisms of senescence and SASP and its impact on radioresistance.